Between ICMI and NU: The Contested Representation of Muslim Civil Society in Indonesia, 1990-2001 - Arskal Salim (Al-Jami'ah: Journal of Islamic Studies, 2011)
This article discusses the concept of Muslim civil society in Indonesia by looking at differences in context between democratic and non-democratic regimes and by considering the diversity of Islamic interpretation of civil society and democracy. By looking at the dynamics within state-society relations and the process of democratisation, this article aims to clarify what kind of political actions correspond to the concept of civil society and help build a strong civil society in Indonesia in 1990s. Limiting its scope to the period from 1990 to 2001, the paper draws on two Muslim organisations (Nahdlatul Ulama and Ikatan Cendekiawan Muslim Indonesia) to explain why do Indonesian Muslims use the concept of civil society differently? How should Muslims perceive civil society vis-à-vis the state? Is it cooperation (participation) or opposition? Are both respective views equally legitimate? Given that Islamic doctrine may support the most varied of political outlooks, this study will point out that there is no single interpretation of the relationship between Islam and civil society or democracy. The article thus argues that differences between the two groups represent the diversity of Islamic interpretations of socio-political life.[Artikel ini membahas konsep “civil society” di Indonesia berdasarkan perbedaan konteks antara rejim demokratis dan otoriter serta menganalisis ragam interpretasi Islam mengenai civil society dan demokrasi. Melalui analisis dinamika hubungan rakyat-negara dan proses demokratisasi, artikel ini menjelaskan bentuk sikap politik yang sesuai dengan civil societydan mendorong terciptanya civil society yang kuat pada dekade 1990an di Indonesia. Diskusi dibatasi pada dua organisasi Muslim di Indonesia, Nahdlatul Ulama (NU) dan Ikatan Cendekiawan Muslim Indonesia (ICMI), dan hanya pada rentang 1990 hingga 2001. Pembatasan dilakukan guna menjawab mengapa Muslim di Indonesia menggunakan konsep civil society secara berbeda dan bagaimana mereka memandang bentuk relasi ideal antara negara-civil society; apakah kerjasama (partisipasi) ataukah oposisi? dan apakah kedua bentuk relasi tersebut sama-sama dapat dibenarkan?. Menyimak bahwa ajaran Islam dapat digunakan untuk mendukung berbagai pandangan politik, artikel ini menggarisbawahi bahwa interpretasi mengenai relasi Islam dan civil society/demokrasi adalah beragam. Karena itu, perbedaan antara NU dan ICMI dalam menterjemahkan konsep civil society merupakan cerminan perbedaan dan ragam interpretasi Islam terhadap kehidupan sosial-politik.]